GAYA BAHASA DAN DIKSI PERLAWANAN DALAM SAJAK ORANG LAPAR KARYA W.S. RENDRA: KAJIAN STILISTIKA - Febryana, Mutia; Butar-Butar, Charles (LUMBUNG AKSARA, 2025)
The poem "Sajak Orang Lapar" by W.S. Rendra is a literary work that represents the voice of social resistance against inequality and injustice experienced by the lower classes. This study aims to describe the style of language and diction used by Rendra as a means of expressing social criticism in the poem. The approach used is a stylistic study with a qualitative descriptive method. Data in the form of words, phrases, and sentences containing elements of style of language and diction of resistance were collected through reading and note-taking techniques. The results of the study show that Rendra utilizes the style of language of metaphor, hyperbole, irony, and repetition to emphasize the suffering and social anger of the oppressed. The chosen diction reflects collective awareness of structural inequality and becomes a symbol of resistance against the oppressive system. The conclusion of this study is that the style of language and diction in "Sajak Orang Lapar" function not only as aesthetic means, but also as a medium for social and moral advocacy for society.